Impact of a CBPR-informed physical activity intervention before and during COVID-19 among women from a disadvantaged neighborhood in Sweden - Ramji, Rathi; Carlson, Elisabeth; Kottorp, Anders; Rämgård, Margareta (Frontiers in Public Health, 2022)
Background: Public health practitioners have been striving to reduce the social gradient and promote physical activity among citizens living in disadvantaged neighbourhoods. The emergence of the COVID-19 pandemic which has affected these citizens extensively has posed a significant challenge to efforts to maintain a physically active lifestyle. Thus, the aim of this study was to explore the impact of a CBPR-informed physical activity intervention before and during COVID-19 from the perspective of women from a socially disadvantaged neighbourhood. Methods: Thirty-four women participated in a CBPR-informed physical activity intervention previously developed in collaboration with lay health promoters and other citizens from the same neighbourhood. Focus group discussions were conducted at four-time points including at baseline prior to intervention start, post-intervention, six months after the intervention ended, as well as during the COVID-19 pandemic. The data were analysed using qualitative content analysis with an inductive approach. Results: Four themes emerged from the discussions including “Wavering between frustration and action”, “Shifting from prioritizing family needs to taking control of self”, “Between isolation and social support” and “Restricted access to health-related knowledge vs utilizing internalized knowledge”. Conclusion: The results of this study reveal that building on CBPR-informed health promotional initiatives has the potential to foster individual empowerment and assist during acute situations like the COVID-19 pandemic through mobilizing communities and their resources which leads to increased community resilience and health. This study is regarded as unique in that it involves evaluation of a CBPR intervention that was initiated ahead of the pandemic and followed even during the ongoing pandemic.